Causes of Divorce Before Marriage Ceremony and Its Relationship with Communication Skills of Divorcees Reviewing The Family Reform Offices in Jordan - Otoum, Saba Hussein Ubdulkareem; Banat, Sohaila (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the causes of divorce before marriage ceremony and its relationship with communication skills of divorcees reviewing the family reform offices in Jordan. the sample of the study consisted of (100) divorcees reviewing the family reform offices in Jarash governorate during the year (2020). To achieve the objectives of the study was developed the causes of divorce before marriage scale and communication skills scale, Semantics were verified Validity and reliability for both scales. The results showed that the most common causes for divorce before marriage the entering the family reform offices in Jarash were the subjective causes, followed by the family causes, while the social causes were the least common for them. The results also showed that the level of communication skills of the divorcees reviewing the family reform offices in Jerash was low, and the results also showed that there were no statistically significant differences in the causes for divorce before marriage ceremony and the communication skills of divorcees reviewing the family reform offices in Jarash due to the variables of gender and age. The results also showed the existence of a statistically significant negative correlation between the causes for divorce before marriage ceremony and the communication skills of the divorcees reviewing the family reform offices in Jarash. The study recommended examining the relationships between the causes for divorce before marriage ceremony and the communication skills among other populations in the Jordanian society and using other divorcee’s samples.